Impact of gate metals/high-K materials and lateral scaling on the performance of AlN/GaN/AlGaN-MOSHEMT on SiC wafer for future microwave power amplifiers in RADAR & communication systems - Gauri Deshpande; J. Ajayan; Sandip Bhattacharya; B. Mounika; Amit Krishna Dwivedi; D. Nirmal (Results in Engineering)
An innovative GaN-channel MOSHEMT (Metal-oxide-semiconductor-high-electron-mobility-transistor) featuring AlGaN aback barrier and AlN barrier is reported. The impact of high-K dielectric materials (HfO2: K = 25, ZrO2: K = 30 and TiO2: K = 80), oxide thickness (tox), gate metals (Al: ϕm=4.3 eV, Ti: ϕm=4.33 eV, Mo: ϕm=4.6 eV, Au: ϕm=5.1 eV, Ni: ϕm = 5.15 eV, Ir: ϕm = 5.27 eV & Pt: ϕm = 5.65 eV) and lateral scaling effects (LGS: Source (S) to Gate (G) distance & LGD: Drain (D) to Gate distance) on the DC & RF behaviour of LG = 100 nm (gate length) GaN-channel MOSHEMT featuring R-Gate, AlGaN-back barrier and AlN barrier is investigated at 300 K using TCAD tool. For tox = 3 nm, the MOSHEMT with HfO2, ZrO2 and TiO2 gate oxides offered a peak transconductance (gm,peak) of 449.1 mS/mm, 469.8 mS/mm and 546.6 mS/mm, a peak drain current (IDS,peak) of 2.24 A/mm, 2.16 A/mm and 1.64 A/mm and a fT (cut off frequency) of 208 GHz, 205 GHz and 190 GHz, respectively. Additionally, it is observed that the downscaling of tox results in a positive shift in VTH (threshold voltage), an improvement in gm,peak and fT, and a decline in IDS,peak. The gm, peak, and fT of MOSHEMTs are not greatly affected by the different gate metals; however, gate metals with smaller ϕm provided the best IDS,peak. Moreover, a positive shift in VTH is seen when ϕm is raised from 4.3 eV to 5.65 eV Due to the suppression of parasitics, the device with lower LGS (300 nm) and lower LGD (800 nm) imparted improved DC/RF behaviour.